Cover Picture: Specific Design of Titanium(IV) Phenolato Chelates Yields Stable and Accessible, Effective and Selective Anticancer Agents (Chem. Eur. J. 29/2016). Issue 29 (3rd June 2016) - Meker, Sigalit; Braitbard, Ori; Hall, Matthew D.; Hochman, Jacob; Tshuva, Edit Y.
Abstract : Titanium phenolato anticancer complex of a single hexadentate tetraanionic ligand aced it all! It is stable for weeks in biological environments, with negligible loss of activity after preincubation for days in medium and serum; it is widely effective in vitro towards 56 cell lines and in vivo in murine models; it is biologically accessible, demonstrating its activity in vitro and in vivo without formulations; it is markedly selective to cancer cells, with no clinical signs of toxicity to treated animals, and indications of apoptotic pathways involved. More information can be found in the Full Paper by E. Y. Tshuva et al. onpage 9986 ff.